AWARENESS OF DIABETES MELLITUS AMONG GENERAL PUBLIC IN SHAH ALAM, MALAYSIA: A CROSS-SECTIONAL STUDY - Qamar, Muhammad; Rashid, Raiz; Ahmad, Sohail; Shaikh, Faiz Ahmad; Ismail, Nahlah Elkudssiah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Despite the improved healthcare and frequent community-ridden educational awareness campaigns, the prevalence of diabetes is enormously increasing and 50% of the Malaysian adults with diabetes are still unaware of their disease status. Therefore, this study aimed to assess the awareness of diabetes mellitus (DM) among the general public of Shah Alam, Malaysia. Methods: A cross-sectional study was carried out in five urban areas of Shah Alam. A total of 350 participants were conveniently recruited using a pre-validated questionnaire. The questionnaire comprised two main parts, including the sociodemographic characteristics of the respondents and a 24-item Diabetes Knowledge Questionnaire. The data were analyzed by Statistical Package for the Social Science® using descriptive and inferential statistics. Results: The overall mean (±standard deviation) score of DM knowledge of participants was 11.11±6.09. Among 350 respondents, more than half claimed that medication is more important than lifestyle modification in DM management. 81.7% did not know about the frequent urination and thirst are signs of DM. 82.3% had a misconception that diabetes is caused by failure of the kidneys to keep sugar out of the urine. The knowledge score was statistically significant difference across the categories of level of education, monthly income, occupations, and family history of diabetes. Conclusion: Majority of enrolled respondents possessed moderate level of awareness and misconceptions regarding diabetes and its management. Hence, there is a need for collective efforts toward improving the level of awareness through community awareness campaigns, to improve the self-management of DM.